Identification of New Fungal Peroxisomal Matrix Proteins and Revision of the PTS1 Consensus. (22nd August 2016) - Nötzel, Christopher; Lingner, Thomas; Klingenberg, Heiner; Thoms, Sven
Abstract : The peroxisomal targeting signal type 1 (PTS1) is a seemingly simple peptide sequence at the C‐terminal end of most peroxisomal matrix proteins. PTS1 can be described as a tripeptide with the consensus motif [S/A/C] [K/R/H] L. However, this description is neither necessary nor sufficient. It does not cover all cases of PTS1 proteins, and some proteins in accordance with this consensus do not target to the peroxisome. In order to find new PTS proteins in yeast and to arrive at a more complete description of the PTS1 consensus motif, we developed a machine learning approach that involves orthologue expansion of the set of known peroxisomal proteins. We performed a genome‐wide in silico screen, characterised several PTS1‐containing peptides and identified two new peroxisomal matrix proteins, which we named Pxp1 (Yel020c) and Pxp2 (Yjr111c). Based on these in silico and in vivo analyses, we revised the yeast PTS1 consensus which now includes all known PTS1 proteins. Abstract : The peroxisomal targeting signal type 1 (PTS1) is the prevalent PTS. Its current definition, however, is largely incomplete. We have modelled PTS1 by a machine learning approach in yeast. Based on this, we identified two conserved genes encoding novel peroxisomal proteins and we updated the consensus motif to now include all PTS1 proteins in yeast.